(untitled) (Research Nepal Journal of Development Studies, 2018)
This paper analyzes agricultural development in terms of policy and implementation in Nepal. More than two-thirds populations in Nepal reside in the rural area and most of them depend on agriculture. Subsistence form of agriculture is common in Nepal. Rural Area and agriculture are interrelated; like two parts of the same coin. The contribution of agriculture to national Gross Domestic Product is remarkable; however, it is declining over the decades. In fact, the agricultural sector cannot attract young people; the trend of migration from rural to urban is significantly increasing. The poverty is exceedingly marked in rural Nepal. The Government of Nepal emphasizes agriculture development in for poverty alleviation. Order to alleviate poverty, rural development, and national economic growth through the policy level. However, available data and qualitative analysis reveal that the outcome from the agricultural sector is not satisfactory due to several factors. In such situation, more than half of the population has been facing food insufficiency. Because of weak policy and implementation, the agriculture sector s been suffering poor outcome. In that way, the government of Nepal along with concerned authorities should effectively implement agriculture policies in order to reduce poverty and rural development. The agriculture-rural accommodating policies and successful performance are crucial for poverty alleviation and rural development.